Assessment of nursing records on cardiopulmonary resuscitation based on the utstein model - Grisante, Daiane Lopes; Silva, Andrea Braz Vendramini; Ayoub, Andrea Cotait; Belinelo, Renata Guzzo Souza; Onofre, Priscila Sete de Carvalho; Lopes, Camila Takao (Rev Rene, 2013)
Cross-sectional study that assessed the quality of nursing records on cardiopulmonary resuscitation. Forty-two patients’ charts were reviewed in an intensive care unit, using the Utstein protocol. There was a predominance of men (54.8%), aged from 21-70 years old (38.1%), correction of acquired heart diseases (42.7%), with more than one pre-existing device (147). As immediate cause of cardiac arrest, hypotension predominated (48.3%) and as the initial rhythm, bradycardia (37.5%). Only the time of death and time of arrest were recorded in 100% of the sample. Professional training in Advanced Life Support was not recorded. The causes of arrest and initial rhythm were recorded in 69% and 76.2% of the sample. Chest compressions, patent airway obtainment and defibrillation were recorded in less than 16%. Records were considered of low quality and may cause legal sanctions to professionals and do not allow the comparison of the effectiveness of the maneuvers with other centers.DOI:https://doi.org/10.15253/2175-6783.20130006000014